Relevansi Positivisme Hukum terhadap Rasionalitas Ilmu Hukum dan Praktik Penegakan Hukum - Yenny Febrianty; Nadya Restu Ryendra; Vasco Javarison Zacharias (Yayasan Pendidikan Kardin Assidiq, 2025)
This study examines the relevance of legal positivism to the rationality of legal science and its impact on law enforcement practices in Indonesia. The research focuses on two central questions: how positivism is implemented in the development of legal science and how it is applied in law enforcement practice. The study employs a normative juridical method, utilising an approach that analyses legislation, doctrinal writings, legal principles, and theoretical perspectives from prominent legal scholars. This framework enables a systematic analysis of positivism as the dominant paradigm that shapes legal reasoning in both academic inquiry and institutional enforcement mechanisms. The findings suggest that the prevalence of positivism in legal scholarship fosters a reductionist tendency, where legal science primarily evolves as a practical discipline focused on normative texts and legal-dogmatic interpretation techniques. This focus limits the development of a more reflective, critical, and interdisciplinary approach. Although positivism contributes a logical order to legal methodology, the combination of empirical observation and formal logic is insufficient to capture the complexity of the social realities underlying the law. Therefore, the positivist framework requires complementary elements such as intuitive reasoning, holistic perspectives, and sensitivity to social dynamics. In the realm of law enforcement, the dominance of positivism results in a strong emphasis on rules, procedures, and administrative formalities. As a result, law enforcement practices can become disconnected from societal needs and the pursuit of substantive justice. While certainty positivism's primary value provides a transparent and predictable normative structure, the rigid application of this approach risks transforming the law from an instrument of justice into merely a mechanism for procedural compliance. Overall, this study concludes that the application of positivism in legal science and law enforcement presents both advantages and limitations. While positivism offers logical coherence and normative certainty, it must be balanced with reflective, contextual, and humanistic approaches to allow the law to develop comprehensively and achieve social justice.